Does Hamulotomy during Palatoplasty Have Any Effect on Hearing Ability in Nonsyndromic Cleft Palate Patients? A Prospective, Single Blind, Comparative Study - Anuj Jain; Pranali Nimonkar; Nitin Bhola; Rajiv Borle; Anendd Jadhav; Shishir Sharma; Shrenik Oswal (Scientifica)
The primary goal of palatoplasty is to achieve a tension-free palatal closure ensuring no postoperative complications. Many surgeons fracture the pterygoid hamulus to minimize tension during palatoplasty. However, this maneuver gained criticism by some authors on the grounds that it may lead to Eustachian Tube dysfunction. Our study intended to figure out the relationship of hamulus fracture with the postoperative state of middle ear in cleft palate children. Fifty consecutive cleft palate patients with an age range of 10 months to 5 years were recruited. All the patients were assigned to either hamulotomy or nonhamulotomy group preoperatively. The patients were subjected to otoscopic examination and auditory function evaluation by brainstem evoked response audiometry (BERA) preoperatively and 1 month and 6 months postoperatively. Otoscopy revealed that the difference in the improvement of middle ear status in both groups was statistically insignificant. Moreover, there was no significant difference in the BERA outcomes of the fracture and nonfracture populations. Complication rate in both groups was also statistically not significant. It can be concluded that hamulotomy does not have any effect on the hearing ability in cleft palate population, so hamulotomy can be performed for tension-free closure during palatoplasty.